Connaissances Paysannes Et Prédisposition À Adopter Une Innovation En Agro-Alimentaire : Cas Du Décorticage Mécanique Et De La Fortification En Fer Du Sorgho Dans Le Nord-Bénin - Agossadou, Morest M. T.; Sêgla, Sandrine S.; Adégbidi, Anselme A.; Kayodé, Polycarpe A. P. (European Scientific Journal, ESJ, 2018)
The consumption of meals prepared from unshelled sorghum derivatives is a factor favoring iron deficiency anemia among consumers. Mechanical dehulling and iron fortification of sorghum appears as a palliative solution. This study has a dual purpose. First of all, it is a question of assessing consumers’ knowledge of sorghum meals with regard to anemia and its causes. Descriptive statistics have been used for this purpose. Then, it was discussed to analyze the determinants of the predisposition of these consumers to adopt mechanical dehulling and iron fortification of sorghum. To do this, the Logit econometric model was used. According to the results, anemia is caused by factors such as malaria, malnutrition, witchcraft, non-respect of fetishes, etc. In addition, households’ propensity to adopt innovation is positively influenced by the income of the chef-cuisine, the perception that it has of its social status after the adoption of innovation and the compatibility of it with norms and values of the household. However, it is negatively influenced by the participation of the chef-cuisine in the experimentation phase and by the perceived complexity of the innovation.